The Use of Intra-Aortic Balloon Pump: IABP - Tocharoenchok, Teerapong; Lerdpunnapongse, Pichej (Siriraj Medical Bulletin, 2021)
In recent decades, tremendous advances have been achieved in intensive care of patients with cardiogenic shock; however, mortality and morbidity from resultant multiple organ failure remain high. Intra-aortic balloon pump has been the most widely used equipment among mechanical circulatory support devices to help patients stabilize hemodynamics and recover from cardiogenic shock from various etiologies for over half of the century. This device enhances organs and coronary perfusion pressure, reduces left ventricular afterload, and increases the cardiac output by working in synchronization with the cardiac cycle and aortic valve mechanic. In this article, we will highlight the principle of counterpulsation, the recent innovation, which has been greatly developed, including hardware and software, current roles, the latest evidence, technical details of the device usage and patient care, weaning guideline, safe removal, and potential complications of the said device. The distinctive use of an extracorporeal membrane oxygenator in comparison with and conjunction with intra-aortic balloon therapy will also be discussed. To help patients stabilize hemodynamics and recover from critical cardiogenic shock or ischemia-reperfusion injury during the cardiac intervention, detailed knowledge is essential for the medical team to establish the position of the counterpulsation device in this high-risk patient subgroup.